PEER GROUP LEARNING DALAM BUDAYA MASYARAKAT PANDALUNGAN TANGGUH BENCANA - Rizeki Dwi Fibriansari; Arista Maisyaroh; Eko Prasetya Widianto; Saifuddin Kurnianto (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2022)
Natural disasters are natural disasters caused by natural events, including earthquakes, tsunamis, volcanic eruptions, floods, droughts, hurricanes, and landslides. The disasters that occurred in Indonesia have claimed hundreds or even thousands of human lives and hundreds of infrastructure damaged by disasters, one of which is an earthquake. Earthquakes are natural events whose time and place of occurrence cannot be predicted. Although earthquakes are prone to occur in the ring of the fire, where and when they will occur cannot be scientifically determined. Therefore, there is a need for natural disaster mitigation that is socialized to the public. This service aims to carry out disaster response lessons for the Pandalungan community. The method used in the service is the field study practice method and learning practicum through training through lectures, discussions, and simulations as well as mentoring. This activity is carried out by providing health education on the management of earthquake emergencies, and disaster simulation activities. Efforts to increase community knowledge and skills in dealing with earthquake emergencies can be carried out by providing counseling and simulations as well as emergency skills training, especially for the community on the slopes of Mount Semeru. This simulation activity is expected to be natural disaster mitigation so that it can reduce victims in the event of a natural disaster.